2017
DOI: 10.5530/ijopp.10.2.24
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Obesity and its Co-Morbidities: A Study Among Thattankuttai Population of Namakkal District, India

Abstract: Background:In the past few decades the issue of overweight and obesity has become a serious public health concern throughout the world. In India, 5% of the population is obese. Obesity is not an immediately fatal disease by itself, but is a risk factor for wide range of serious non communicable diseases in Indian population. Aims: This study was aimed to investigate the prevalence of obesity in a rural village, Thattankuttai population at Namakkal district, Tamil Nadu, India and to evaluate its relationship wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…[2122] Among the study participants, 64.1% of the study participants were found to be overweight/obese while in studies done by Karthik et al and Prasad et al , the prevalence of obesity was found to be 49.8% and 62%, respectively. [2324] This higher prevalence of obesity may be attributed to the fact that majority of the study participants (77.1%) were housewives who might be having a sedentary lifestyle. The high prevalence of obesity among women in reproductive age group increases the risk of developing ovulatory problems, poor compliance to oral contraceptive pills, miscarriage, urinary incontinence, fibroids, and menstrual problems.…”
Section: Discussionmentioning
confidence: 99%
“…[2122] Among the study participants, 64.1% of the study participants were found to be overweight/obese while in studies done by Karthik et al and Prasad et al , the prevalence of obesity was found to be 49.8% and 62%, respectively. [2324] This higher prevalence of obesity may be attributed to the fact that majority of the study participants (77.1%) were housewives who might be having a sedentary lifestyle. The high prevalence of obesity among women in reproductive age group increases the risk of developing ovulatory problems, poor compliance to oral contraceptive pills, miscarriage, urinary incontinence, fibroids, and menstrual problems.…”
Section: Discussionmentioning
confidence: 99%